Hydrolyzed Polyacrylamide Screening for EOR in an Indonesia Mature Oil Field - Erfando, Tomi; Siregar, Gerry; Alli, Yani Faozani; Wangge, Yohanes B. D. (Trends in Sciences, 2022)
Most of Indonesia’s oil field has been producing the oil for long period of time. For this reason, enhanced oil recovery (EOR) method becomes the most promising method to improve oil production for the country. Chemical flooding, especially polymer flooding is the simplest and the most commonly applied chemical enhanced oil recovery technique, since it can be used after water flooding process. Screening is considered the first step in evaluating and selecting potential polymers for reservoirs. Therefore, this paper aims to select partially Hydrolyzed Polyacrylamide (HPAM) base polymers to find suitable polymer for a targeted mature reservoir in Indonesia. A polymer screening study was carried out on 3 HPAM polymers to identify a potential candidate which can withstand reservoir conditions. These are Kerui, Zekindo, and FP 3630S. Initially, a comprehensive rheological (viscosity, shear rate) study was conducted at various polymer concentrations (500 - 2500 ppm) and brine to investigate the polymers. Then, filtration and screen factor test was conducted at various concentrations (1000 - 2000 ppm). Then, a thermal stability test was conducted at anaerobic condition and 140 °F for 2 months. Finally, for oil recovery used core flooding test. Based on the result of the test, FP 3630S with a concentration of 2000 ppm was chosen for the core flooding test. The test was designed in 3 steps: At first, water injected into the sample, followed by polymer-solvent at 2000 ppm concentrated of 1 PV, the finally injected by water. The results of core flooding showed oil recovery of 28.93 % OOIP. Finally, this study was performed to develop screening criteria and to correlate oil recovery prediction. HIGHLIGHTS One of the efforts to increase old field production is by choosing the right type of polymer to be injected Polymer screening was carried out through testing stages, namely rheology, filtration and screen factor, thermal stability, and core flooding Selected one type of polymer that meets all the qualifications of the screening tests GRAPHICAL ABSTRACT